(untitled) (Raparin Journal of Humanities (RJH), 2023)
The aims of this research are to determine the level of utilizing active learning strategies and their relationship to self-organization among kindergarten teachers in Erbil city center. Also to determine the relationship between active learning strategies and self-organization among kindergarten teachers according to variables (degree، years of service). The research methodology is appropriate to the nature of the aim of the current research. The population consists of a kindergarten teachers of Erbil Central Education for the academic year (2022–2023)، in where their number are (578) teachers distributed over (49) kindergartens. The selected sample were (150) teachers from (15) public kindergartens in the center of Erbil. To achieve the aims and collect data، the researcher use two sets of questionnaire for the teachers in the kindergarten for the academic year 2022-2023. The first question are includes 42 items investigate the active learning strategies which adopted from (Saleh، 2016) . while the second questionnaire was adopted from (Bandy More، 2010) which consists of 36 item on self - organization. The researcher issued the honesty of both research tools by providing a number of experts and experts، (87%) for the criterion of active learning strategy and (85%) to regulate the self، criteria (90%) for active learning strategy (83%). To organize self-acquisition using the Person related equation equation. The main result revealed that. The level of use of active learning strategies among kindergarten teachers was high، had a positive and effective effect on self-organization among kindergarten teachers، and kindergarten teachers pay attention to active learning strategies during teaching.